2017
DOI: 10.1038/srep42786
|View full text |Cite
|
Sign up to set email alerts
|

Calcium spikes, waves and oscillations in a large, patterned epithelial tissue

Abstract: While calcium signaling in excitable cells, such as muscle or neurons, is extensively characterized, calcium signaling in epithelial tissues is little understood. Specifically, the range of intercellular calcium signaling patterns elicited by tightly coupled epithelial cells and their function in the regulation of epithelial characteristics are little explored. We found that in Drosophila imaginal discs, a widely studied epithelial model organ, complex spatiotemporal calcium dynamics occur. We describe pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
95
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 72 publications
11
95
2
Order By: Relevance
“…Calcium also plays a significant, but poorly understood role in development of the wing disk. Strong phenotypes, including blistered or bent wings, result when Ca 2+ signaling is perturbed (Balaji et al, ; Brodskiy et al, ; Dahal et al, ; Dahal, Pradhan, & Bates, ). Ca 2+ is a second messenger, and Ca 2+ signaling networks often exhibit a “bow‐tie” structure in that the integrated effect of many inputs is governed by a small number of molecules in the calcium pathway, and they affect many outputs (Brodskiy & Zartman, ), similar to the way that many growth‐affecting factors impinge upon the Hippo kinase cascade.…”
Section: Biochemical Regulation Of Growth and Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium also plays a significant, but poorly understood role in development of the wing disk. Strong phenotypes, including blistered or bent wings, result when Ca 2+ signaling is perturbed (Balaji et al, ; Brodskiy et al, ; Dahal et al, ; Dahal, Pradhan, & Bates, ). Ca 2+ is a second messenger, and Ca 2+ signaling networks often exhibit a “bow‐tie” structure in that the integrated effect of many inputs is governed by a small number of molecules in the calcium pathway, and they affect many outputs (Brodskiy & Zartman, ), similar to the way that many growth‐affecting factors impinge upon the Hippo kinase cascade.…”
Section: Biochemical Regulation Of Growth and Patterningmentioning
confidence: 99%
“…Ca 2+ is a second messenger, and Ca 2+ signaling networks often exhibit a “bow‐tie” structure in that the integrated effect of many inputs is governed by a small number of molecules in the calcium pathway, and they affect many outputs (Brodskiy & Zartman, ), similar to the way that many growth‐affecting factors impinge upon the Hippo kinase cascade. Like Hippo, growth and mechanical signals both affect Ca 2+ (Antunes, Pereira, Cordeiro, Almeida, & Jacinto, ; Balaji et al, ; Brodskiy et al, ; Narciso et al, ; Narciso, Contento, Storey, Hoelzle, & Zartman, ; Restrepo & Basler, ). Ca 2+ signaling in the wing disk exhibits a rich variety of dynamical behaviors.…”
Section: Biochemical Regulation Of Growth and Patterningmentioning
confidence: 99%
“…It is unlikely that the establishment of gap junctions is involved in this time window, as calcium waves could already be experimentally induced several hours earlier (Hunter et al 2014). In Drosophila, soluble extract of wing disc triggers calcium epithelial waves (Balaji et al 2017) and morphogen regulates their amplitude and frequency (Wu, Brodskiy, Huizar, et al 2017). It is possible that the secretion of a specific molecular component controls the embryonic calcium waves described here.…”
Section: Discussionmentioning
confidence: 89%
“…A potential explanation for similar outcomes in Dpp and Ca 2+ after Irk channel inhibition is that intracellular Ca 2+ dynamics regulate Dpp release, although whether or not Ca 2+ has a causative effect requires further study. Several studies have shown that Ca 2+ is crucial to regulation of epithelial physiology during development . However, whether Ca 2+ directly regulates Dpp secretion is currently unknown.…”
Section: Morphogen Sources Are Dynamic and Controlled By Physiologicamentioning
confidence: 99%
“…Several studies have shown that Ca 2+ is crucial to regulation of epithelial physiology during development. [45][46][47][48][49][50] However, whether Ca 2+ directly regulates Dpp secretion is currently unknown. Given that misregulation of Ca 2+ is frequently associated with developmental genetic disorders resulting in neoplasms, 51 it is necessary to further characterize the roles of Ca 2+ and other second messengers in morphogen transport and morphogenesis to provide insight into therapies to treat these genetic disorders.…”
Section: Morphogen Sources Are Dynamic and Controlled By Physiologimentioning
confidence: 99%